2023
DOI: 10.1002/pssa.202200900
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Degradation of Commercial Ultraviolet‐C Light‐Emitting Diodes for Disinfection Purposes

Abstract: Herein, the reliability of commercial ultraviolet‐C (UV‐C) light‐emitting diodes (LEDs) subjected to constant current stress is reported. Electrical, optical, and spectral analyses are carried out on UV‐C LEDs with an emission peak of 275 nm and a nominal optical power of 12 mW at 100 mA. Degradation tests are carried out at the maximum rated current, the double and at three times the maximum. The LED lifetime is found to be inversely proportional to the third power of the stress current density, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The interest towards ultraviolet Light-Emitting Diodes (LEDs) is rapidly increasing [1], thanks to the wide field of applications, including water purification, sterilization, surface curing, monitoring of emissions, and lithography. The UVC spectral range (200-280 nm) is of great interest, and can also be used to inactivate viruses and bacteria, including the SARS-CoV-2 [2,3]. Remarkably, it has been shown that the spectral region between 200 nm and 235 nm is safe for exposure, while at the same time being effective for virus inactivation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The interest towards ultraviolet Light-Emitting Diodes (LEDs) is rapidly increasing [1], thanks to the wide field of applications, including water purification, sterilization, surface curing, monitoring of emissions, and lithography. The UVC spectral range (200-280 nm) is of great interest, and can also be used to inactivate viruses and bacteria, including the SARS-CoV-2 [2,3]. Remarkably, it has been shown that the spectral region between 200 nm and 235 nm is safe for exposure, while at the same time being effective for virus inactivation [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…LED degradation mechanisms related to electroluminescence reduction are the subject of many scientific studies, most of which concern low-power LEDs or elements outside the UVC range [19]. In recent years, in the scientific literature, several reliability analyses (Table 2) and lifetime estimations [19][20][21][22][23][24][25][26][27] of low-power UVC LEDs were published. A variety of operation conditions were assumed.…”
Section: Introductionmentioning
confidence: 99%
“…The first mechanism is associated with the complete lack of emission of optical radiation, while the second is associated with its successive loss and from the operational point of view is a significant problem because, despite the actual operation of the system, it leads to a deterioration in the effectiveness of the disinfection process [22]. The gradual degradation of the OP of LED depends on the operating temperature and current density [22,[28][29][30][31][32] and is the fastest during the first 10-200 h of operation, then the process slows down [19,21,[33][34][35][36][37]. According to [22,38], the UVC LED's lifetime is inversely proportional to the third power of the stress current density.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations